INTERNALISASI PENDIDIKAN KARAKTER ISLAMI MELALUI PROGRAM TAHFIZD AL QUR’AN DI TK IT BUAH HATI - Junaidi Junaidi; Purniadi Putra; Sri Sunantri (CV. ADIBA AISHA AMIRA, 2024)
The main purpose of learning tahfidz Al Qur’an is the formation of personality in the students themselves which is reflected in their behavior and mindset in daily life, then learning tahfidz Al Qur’an is not only the responsibility of the tahfidz Al Qur’an alone, but it requires the support of the entire community at school, society, and more importantly is the parent because the Qur'an as a guide to the lives of Muslims that we must read and practice. This research uses a qualitative approach. While the method of data collection uses observations, interviews, field notes and study documents. The results of this study can be stated that the character values that can be instilled in students through the study of tahfidz Al Qur’an include honest, diligent, disciplined, sincere, patient, hard work, hard work, istiqomah and responsibilities that are applied in life . The method used in memorizing the Qur'an in TKIT Buah Hati is to use the muraja'ah method (to repeat memorization that has been played before the teacher), the sima'i method (to hear the meaning of this method by students listening to something to memorize, and the talaqqi method (depositing or listening to memorization that was just memorized to a teacher). The formation of character through the study of tahfidz of the Qur'an besides being part of the process of forming noble morals, is expected to be the main foundation in increasing the degree and dignity of students as children of the nation. The formation of a balanced, healthy and strong human personality is strongly influenced by religious education and the internalization of religious values in students. The formation of students' Islamic character at TKIT Buah Hati Sintang is carried out by the method of delivery, habituation, exemplary, reprimand, and the provision of rewards and punishment.